PERAN CITRA MEREK MEMEDIASI PENGARUH KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN (STUDI PADA KONSUMEN PRODUK TEH BOTOL SOSRO DI KOTA DENPASAR) - Maharani, I Gusti Putu Diva; Satria Pramudana, Komang Agus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.09.TAHUN.2024DO - 10.24843/EEB.2024.v13.i09.p19, 2024)
The increment in the food and beverage industry affects society's consumption level, especially in Denpasar City ranks in the highest position of food and non-food consumption in Bali. One of the local products engaged in this industry field and is well-known by society is Teh Botol Sosro. This study aims to explain the role of brand image mediates the effect of product quality on customer loyalty. This study was conducted in Denpasar City by involving 130 respondents using a purposive sampling technique. The data analytic technique that was used is the descriptive statistical analysis technique, the classic assumption test, the path analysis, and the sobel test. This study shows that product quality has a positive and significant effect on the brand image of Teh Botol Sosro consumers in Denpasar City. A product quality affects a positive and significant effect on customer loyalty of Teh Botol Sosro products in Denpasar City. A brand image affects a positive and significant effect on customer loyalty of Teh Botol Sosro products in Denpasar City. A brand image positively and significantly mediates the effect of product quality on customer loyalty of Teh Botol Sosro products in Denpasar City. This study is expected to give an empirical contribution regarding the relationship between quality product, brand image, and customer loyalty variables in marketing science development.